WATER STRESS EFFECTS ON CHLOROPHYLL FLUORESCENCE AND CHLOROPHYLL CONTENT IN SUGARCANE CULTIVARS WITH CONTRASTING TOLERANCE - Silva, Marcelo de Almeida [UNESP]; Pincelli, Renata Passos [UNESP]; Barbosa, Alexandrius de Moraes (Univ Federal Uberlandia, 2018)
One way to minimize the impacts caused by water deficit (WD) in agriculture is the use of tolerant cultivars. The physiological evaluation of plants through the potential quantum efficiency of photosystem II (Fv/Fm) and estimated chlorophyll content (SPAD index) can be an effective tool in the selection and recommendation of water deficit-tolerant cultivars. Within this context, the aim of this study was to evaluate the physiological responses of sugarcane cultivars classified as tolerant or susceptible to water deficit. The experiment was carried out near the city of Jau, SP, Brazil in a greenhouse, between July and December 2013. The experimental design was completely randomized in a 4 x 2 factorial arrangement, with four replications. We studied four sugarcane cultivars: RB72454, RB855453 (prone to WD), SP81-3250 and SP83-2847 (WD-tolerant) in two water management regimes (with and without deficit). WD reduced stems dry mass of all cultivars, however, the greatest decreases were observed in susceptible cultivars to WD, where the decrease was 58.3 and 74.5% for cultivars RB855443 and RB72454, respectively. As for the SP81-3250 and SP83-2847 cultivars (tolerant), the reduction was 44.1 and 47.7%, respectively. For water deficit-tolerant cultivars, there was lower reduction in potential quantum efficiency of photosystem II and SPAD index; therefore, the physiological characteristics (Fv/Fm and SPAD index) are features that can aid the identification and selection of water deficit tolerant cultivars, and also help the recommendation of these cultivars for harsh environments, minimizing the effects of water deficit on stem yield on the sugarcane crop.
Keywords: Saccharum spp.; SPAD index; Water stress; Potential quantum efficiency of photosystem II; Photosynthetic pigments